Examining Language Teacher Readiness for Blended Learning among Cycle-one Public Schools in the UAE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This qualitative study sought to explore cycle-one (primary-level) language teacher perceptions of blended learning in the UAE. Given the recent shift to online learning, in response to the global COVID-19 pandemic, this exploratory research sought to ascertain pertinent information to assist decision-makers and educational leaders. Specifically, the researchers addressed what teachers perceived to be facilitators of and barriers to implementing effective blended learning instruction in public, cycle one schools in the UAE. They also sought their perspectives concerning effective strategies for blended language instructions and how they perceived these strategies influenced students' performance. Toward this end, the researchers utilized face-to-face, open-ended interviews with purposefully selected participants in a phenomenological approach; all data were analyzed via a thematic analysis that employed multiple stages of coding: open, axial, and selective. Findings suggest that teachers perceive parental engagement to be a facilitator in implementing blended learning. Participants also suggest that purposeful planning, instruction, and assessment should be explicitly designed for blended learning environments for more effective language learning. Finally, the teachers in this purposeful sample report that blended learning have influenced students' performance in multiple areas, including academic attainment, character development, and technical skills.